Formation of Interpersonal Competencies Through Interprofessional Simulation: Nursing and Medicine - Baeza-Contreras, M (Lippincott Williams and Wilkins, 2023)
AIM The aim of this study was to analyze the process of interpersonal competencies formation in nursing and medical students who participated in a standardized interprofessional clinical simulation. BACKGROUND Interprofessional education in health sciences has had an important impact on the development of relational qualities centered on the patient. METHOD The study followed a qualitative interpretive approach with students. Students who participated in clinical simulation activities were asked about their experiences and their learning process with respect to interpersonal competencies. A thematic analysis of the data was performed RESULTS Three themes emerged: 1) approaching the practice with uncertainty and fear of new relationships, 2) reflecting on decisions while recognizing distinctive roles, and 3) recognizing the human sense of practice while developing skills for caring and curing. CONCLUSION Students underwent this process and learned about empathy, communication, critical reflexive thinking, and teamwork. © Lippincott Williams & Wilkins.